Simulation Of Acidic Water Purification Process In Refinery Based On Determining Appropriate Operating Conditions - Bey, Mufida (Journal of Pure & Applied Sciences, 2023)
Acidic process water produced by refineries contains some hazardous pollutants such as (H2S and NH3). Acid water extraction units remove both compounds from the water. The removed contaminants are sent to a sulphur recovery unit to produce sulphur and avoid any acid emissions contrary to environmental regulations. Water pollution is a problem that concerns all people in the world. In view of the importance of preserving the environment and water resources, in this research, the simulation of the acid water treatment unit in the refinery was studied using the Aspen Hysys software based on determining the appropriate operating conditions. The NRTL electrolyte activity coefficient model was used to predict the system's thermodynamic behaviour. The simulation results showed that the suitable temperature for the feed entering the tower is about 38°C and the convenient distance for the trays in the disposal tower is 0.54 mm. Under these conditions, the concentration of hydrogen sulphide 0.1694 and 0.2418 of ammonia in the acid gas exiting the tower reaches its maximum at a molar flow rate of the mixture of about 39.86 kgmol/h, according to the economic considerations of the operating tower.